Effects of Diving Experience on Some Biological Variables of Divers - Mohammed Elmaghraby, Ahmed; Mostafa Sakoury, Mona; Ali Mostafa, Sally; RafatAboseta, Mohammed (International Journal of Psychosocial Rehabilitation, 2024)
The current research aims to study the effects of diving for different years on some biological variables of divers. The researchers used the descriptive (survey) approach. The researchers purposefully chose 30 persons divided into divers (n = 20) and non-divers (n = 10). Divers were subdivided into (5-6) years of diving experience (n = 10) and (9-10) years of diving experience (n = 10). Non-divers (n = 10) are not involved in diving or any other athletic activity. Results indicated statistically significant differences among the three groups on the post-measurement of biological variables of pulse, diastolic and systolic blood pressure, percentage of CD34+, and cortisol, in favor of the second and third groups. This means that divers (5-6 years and 9-10 years) were better than non-divers.